Impact of Value-Added Tax (VAT) revenue in major states of India - Mohd. Azam Khan; Nagma Shadab (Romanian Journal of Fiscal Policy (RJFP), 2013)
Value Added Tax (VAT) is a type of indirect tax that is imposed on goods and services. In one of the most important reforms of the country's public finances in over the past 50 years, India has finally launched much delayed Value Added Tax (VAT) from 1st April, 2005 in 21 states. VAT has replaced the existing local sales tax in almost all states of India. The case for state VAT in India has been advocated mainly on the grounds of higher revenue efficiency vis-à-vis the combined revenue from various types of sales/purchase taxes it replaced. The present paper tries to analyze, the impact of VAT on revenue, its buoyancy, and efficiency of states sales tax/value added tax.
Keywords: H25; H2; H21; H7; 330; Sales Tax; Value Added Tax; Revenue Growth; Buoyancy and Indian States